OP42 Glycaemic load and index in pregnancy are associated with postnatal, but not pre-pregnancy, depressive symptoms; longitudinal data from the southampton women's survey. (2nd September 2017) - Inskip, H; Okubo, H; Crozier, S; Cooper, C; Godfrey, K; Robinson, S; Baird, J
Abstract : Background: High glycaemic load (GL) and glycaemic index (GI) diets have been linked to poor health. In cross-sectional studies, associations between GL and GI and psychological disorders have also been identified, though the direction of association has not always been consistent. Few longitudinal data exist and none in relation to associations between GL and GI during pregnancy and postnatal depression. We aimed to assess whether higher GL and GI during pregnancy were associated with increased risk of postnatal depressive symptoms using data from the Southampton Women's Survey (SWS). Methods: The SWS is a population-based cohort study of 12 583 women aged 20–34 years assessed when not pregnant; those enrolled during the latter half of the recruitment period completed the General Health Questionnaire (GHQ-12), a short screening instrument for depressive symptoms. Women who became pregnant (n=3, 158) were followed up. Six months post-partum, mothers completed the Edinburgh Postnatal Depression Scale questionnaire to determine postnatal depressive symptoms. Established cut-offs for each depression scale were used to determine presence of depressive symptoms before and after pregnancy. At 11 and 34 weeks' gestation, diet during the preceding 3 months was assessed using an interviewer-administered food-frequency questionnaire, from which GL and GI were determined. Prevalence ratios (PRs) for postnatal depressive symptoms were obtained using Poisson regression with robust variance. Potential confounding factors were identified through a Directed Acyclic Graph, namely age, educational attainment and smoking during pregnancy. Linear regression was used to assess the relationship between pregnancy GL and GI and pre-pregnancy depressive symptoms. Results: Postnatal depression data were available for 2856 women, with 2038 and 2429 of them having GL and GI data at 11 and 34 weeks' gestation respectively. In univariate analyses, postnatal depressive symptoms were positively associated with GL at both time points and GI at 34 weeks' gestation, but were strongest for 34 weeks' GL: PR 1.12 per 100 GL units (95% CI: 1.04–1.20). After adjustment for confounders, 34 weeks' GL was the only measure associated with postnatal depressive symptoms: PR 1.09 per 100 GL units (95% CI: 1.01–1.17). Notably, there was no association between pre-pregnancy depressive symptoms derived from the GHQ12 and either GL or GI. Conclusion: These findings suggest that improving diet in pregnancy, particularly lowering GL in late pregnancy, might protect against postnatal depressive symptoms. Pre-pregnancy depressive symptoms were not associated with GL and GI in pregnancy indicating that reverse causation is unlikely.